A preliminary study on the impact of household air pollution on adult respiratory health in urban and rural settings of Jaipur, India - Arun Kumar Sharma; Anukrati Dhabahi; S S Mohanty (Wolters Kluwer Medknow Publications, 2024)
Background: This study aimed to investigate the association between household air pollution and chronic respiratory illness (CRI) in Jaipur, India. Materials and Methods: A total of 147 participants over 18 years of age from 45 households were randomly included in the study, and follow-up visits were conducted once every fortnight over a three-month period. Spirometry tests were conducted using a portable hand-held digital spirometer. A self-designed, pretested, semi-structured questionnaire was utilized to collect socio-demographic information from the participants. Statistical tests, such as t-tests were used to analyze the association between household air pollution and CRI. Results: The prevalence of COPD and bronchial asthma was 2% and 4%, respectively. Various risk factors for CRI were identified within households, and only 4 episodes of acute exacerbation of chronic respiratory illness were observed, resulting in no incidence density calculation. The mean values of forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1) were significantly lower in females (P < 0.001) Also, the mean values of FVC and FEV1 were significantly lower in rural areas (P < 0.005) than urban areas. Conclusion: Our findings highlight the importance of government and stakeholder action to implement clean air policies and protect respiratory health. Further studies are needed to expand on these findings and delve deeper into understanding the complex interactions between various risk factors and respiratory health in this population.